Evaluasi Perhitungan, Pemotongan, Penyetoran, Pelaporan, dan Pencatatan PPh Pasal 23 Pada PT. XYZ (Jurnal Riset Manajemen dan Akuntansi, 2025)
The purpose of this study is to evaluate how Article 23 Income Tax is applied to PT XYZ in 2024 in terms of calculation, deduction, deposit, reporting, and recording. This study was conducted using a qualitative descriptive method by applying a documentation study approach to tax reports, accounting journals, deduction reports, and proof of payment. The results of the study prove that the calculation and deduction of taxes have been realized correctly in accordance with the provisions of the 2% rate for rental transactions other than land and buildings. Although the January 2024 tax was postponed by one day, deposits were usually made on time. Reporting of the Article 23 Income Tax Periodic Tax Return (SPT) was carried out on time through the Unification e-Bupot. In addition, tax transactions have been recorded in accounting in accordance with the accrual principle, which ensures the conformity of the company's fiscal and commercial financial reports. Overall, PT XYZ has demonstrated a high level of compliance with applicable tax regulations, although internal supervision of the tax deposit deadline needs to be improved.